Pernikahan Dini dilihat Dari Sudut Pandang Ketahanan Keluarga Desa Rerebe Kecamatan Tripe Jaya Kabupaten Gayo Lues - Duwi Agustina; Mira Fauziah; Rofiqa Duri (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
Early marriage in Rerebe Village, Tripe Jaya District, Gayo Lues Regency has a negative impact on family resilience. The impact of early marriage on couples who marry at an early age and several factors that influence family resilience for couples who marry at an early age in influencing family resilience. This study uses a qualitative approach with a descriptive research type. The qualitative approach was chosen because this study aims to understand in depth the phenomenon of early marriage seen from the perspective of family resilience in Rerebe Village, Tripe Jaya District, Gayo Lues Regency. Based on the results of research conducted on four married couples in total (8 people) who married at an early age in Rerebe Village, Tripe Jaya District, Gayo Lues Regency, it can be concluded that early marriage has a significant negative impact on family resilience in various dimensions, namely economic, social, psychological, and childcare and education dimensions. And there are several factors that influence family resilience.